Testing market integration of staple food stuffs in Borno State, Nigeria - Onyeka, U.P.; Olayemi, J.K.; Kormawa, P.M.; Mafimisebi, T.E. (2006)
The main objective of this study is to test market integrated of staple foodstuff in Borno State. The data used came from a database of International Institute of Tropical Agriculture (llTA) Ibadan. The data were on monthly prices of some selected foodstuff in Borno State and covered a period of nine years (1992-2000). A total of 108 observations were used. A simpler version of bivarate autoregression model was employed in the analysis. The study reveals that contemporaneous and instantaneous price effects have more significant effect. The instantaneous price transmission was less than unity in all cases with values ranging from 0.017 to 0.912. Also, lagged price in the independent market lead to decline in price in the dependent market. Out of 11 pairs of index of market onnection (IMC) values obtained, pepper shows very high degree of marketing efficiency and dependence between the market pairs with values of 1.361 for R? U and 1.07 for U?R while dry okra shows a very low degree of marketing efficiency and dependence between the market pairs with IMC values of 0.875 (R?U) and 0.060 (U?R). Moreso, there is a high degree of market efficiency in the marketing of these staple foodstuffs because of the existence of short-run market integration. We recommend that the provision of the necessary infrastructure like storage, processing, transportation facilities, communication system, access roads will prevent the inefficient allocation and distribution of goods and resources in Borno State, Nigeria.